Application of the Logistics Postponement in a Retail Supply Chain of Wal-Mart : Current Effects and Future Tendencies - Świerczek, Artur (Zastosowanie koncepcji odraczania logistycznego w łańcuchu dostaw Wal-Mart : obecne efekty i przyszłe tendencje, 2009)
The application of new logistical concepts, supported by the intensive use of the advanced information and communication technologies contribute to improving supply chain performance. The significantly positive impact of the combination of logistics and ICT on supply chain performance may be observed in a retail industry. The leading logistical concepts which improved the market position of retail supply chains are a logistics postponement strategy. The practical application of the strategy resulted from the improvement of the customer service level, reducing the costs of logistics operations and higher revenues. The implementation of the postponement strategy should be supported by the operational logistics techniques and modern technology. This paper explores the effects of the dynamic development of innovative logistical concepts, specifically logistics postponement strategy supported by the use of information technology in a retail supply chain. The paper also presents the major tendencies that may occur in future and have an impact on the operational environment of retail supply chains. Key words: logistics, postponement strategy, retail supply chain, Wal-Mart
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 65, s. s. 116-126
Keywords: logistics, postponement strategy; retail supply chain; Wal-Mart